USLUB AL-ILTIFAT FI DIRASAT ULAMA AL-BALAGAH AL-QADIM WAL HADITS - Noor, Damhuri Dj.; Bahri, Ratni Bt. H. (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
The paper discusses the al-Iltifât language style in the Arabic tradition of science. Al-Iltifât is the transition of communication patterns in the conversation. Ontologically, al-Iltifât as a style of the language regarded as the crucial part of balaghah study, because there is no unity of definition and scope of study among scholars, even the names are quite varied. In the tradition of classical study, ulama provide various names. The scope of this al-Iltifât is limited to transition on the use of pronouns, the use of verbs, and the transition of themes in the conversation context. In contrast to modern balaghah scholars who are expanding the scope of the al-Iltifât, they are not bound by the definition and scope of the study proposed by classical scholars. They depart from the general terminology that all forms of communication pattern transition are included in the al-Iltifât category. Therefore, they develop various types that have an impressive communication pattern transition.